Histopathology of the liver of Indin Murrel Channa punctatus (Bloch) exposed to Phenolic Effluents - Alka Mishra; Aditi Poddar (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
The aim of this study was to examine the histological changes in the liver of fish Channa punctatus (Bloch) for a short term (8day) and long term (30 days) exposure in response to the Phenolic Industrial effluents of Bhilai Steel plant. Fishes were exposed in different concentration (low .01%, .015%, .02, .025%) and ( high concentration 10%, 20%, 30%) of Phenolic effluent. Tissu sections of the liver were stained with haematoxyline-eosin and changes in the tissues were examined using light microscope. No histopathological changes were found in control, although no lesions were observed in response to short term exposure to both low and high concentration of toxicants, however remarkable changes in liver structure were observed in response to long term exposure .These included nuclear and cytoplasmic degeneration, leucocytic infiltration, vascular congestion hemorrhage. The degree of damage depended on the concentration of effluents and period of exposure.